PENINGKATAN EKONOMI MASYARAKAT MELALUI INOVASI PRODUK OLAHAN KERIPIK PEPAYA DI DESA STADONG KECAMATAN DAMPAL UTARA - Nabila Basir; Marlina Marlina; Moh Rafly; Rahma Wati; Moh Fadly; Adnan Adnan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Stadong Village, North Dampal District, has abundant papaya potential, but its utilisation is still limited to fresh fruit, resulting in relatively low sales value. This condition causes the community not to obtain optimal profits from the papaya harvest. This community service activity aims to improve the community's economy by innovating papaya chip products with a longer shelf life and higher sales value. The implementation methods include: (1) socialisation of business potential and opportunities, (2) technical training in making papaya chips, (3) business management assistance, and (4) digital-based marketing. The results show increased production skills, increased marketing knowledge, and the formation of small business groups that have begun to market products locally and online. Papaya chip products have been marketed in stalls around the village, received a positive consumer response, and have the potential to become a superior village product. This program has proven effective in increasing the added value of papaya, encouraging community economic independence, and opening opportunities for sustainable business development based on local potential.